2015
DOI: 10.1016/j.nicl.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal gray matter contraction in three variants of primary progressive aphasia: A tenser-based morphometry study

Abstract: The present study investigated the pattern of longitudinal changes in cognition and anatomy in three variants of primary progressive aphasia (PPA). Eight patients with the non-fluent variant of PPA (nfvPPA), 13 patients with the semantic variant (svPPA), seven patients with the logopenic variant (lvPPA), and 29 age-matched, neurologically healthy controls were included in the study. All participants underwent longitudinal MRI, neuropsychological and language testing at baseline and at a 1-year follow-up. Tense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
80
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 115 publications
(186 reference statements)
11
80
1
2
Order By: Relevance
“…The finding by Foxe et al (2013) and Meyer et al (2015) of poorer phonological short-term memory in lvPPA were compared with AD, despite patients being matched for visual short-term memory performance might represent a transient distinction. It is of interest in this regard that longitudinal studies of lvPPA have indicated a convergence over time with the clinical symptoms of AD (Leyton, Hsieh, Mioshi, & Hodges, 2013) and a spread of atrophy consistent with AD (Brambati et al, 2015) (Rohrer et al, 2013). It is possible that at an earlier stage of disease greater differences might have been elicited between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The finding by Foxe et al (2013) and Meyer et al (2015) of poorer phonological short-term memory in lvPPA were compared with AD, despite patients being matched for visual short-term memory performance might represent a transient distinction. It is of interest in this regard that longitudinal studies of lvPPA have indicated a convergence over time with the clinical symptoms of AD (Leyton, Hsieh, Mioshi, & Hodges, 2013) and a spread of atrophy consistent with AD (Brambati et al, 2015) (Rohrer et al, 2013). It is possible that at an earlier stage of disease greater differences might have been elicited between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitively, lvPPA, svPPA, and nfvPPA variants are characterized by core language deficits involving repetition, comprehension, and agrammatism, respectively [1]. Structural neuroimaging studies also highlight distinct, primarily left hemispheric, patterns of atrophy in temporal and frontal lobe structures, across PPA variants [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Damage of these 2 rather distant regions would require large vascular lesions which usually lead to global aphasia in vascular conditions. Regarding agrammatic PPA, it mainly affects Broca's region [23], but lesion extension towards temporal cortices subtending language monitoring has not been reported in imaging studies, including longitudinal investigations on this PPA variant [44].…”
Section: Discussionmentioning
confidence: 98%